Selection and Inheritance of Tomato Resistance against Ralstonia solanacearum - Isna Maulida; Rudi Hari Murti; Triwidodo Arwiyanto (Universitas Gadjah Mada, 2019)
Ralstonia solanacearum is a plant pathogen causes wilting which is a major obstacle in the cultivation of tomato plants. In plant breeding, knowledge of the source of resistance genes and inheritance patterns is important in the development of bacterial wilt resistant varieties. This study aimed to obtain bacterial wilt resistant lines and to find out the inheritance pattern of tomato resistance to bacterial wilt. Selection of resistant plant involved the selected breeding lines from irradiation and crossing collections of the Genetic Laboratory, Faculty of Agriculture, Universitas Gadjah Mada. Introduced lines of H-7996 and F1 Permata and Timoti were used as a control. H-7996 as resistant parents and GM2 as susceptible parents, and their offspring include F1 GM2 x H-7996, F1 reciprocal, F2, Back Cross 1 (F1 x GM2), and Back Cross 2 (F1 x H-7996) used in testing inheritance patterns. Inoculation was carried out 1 week after planting by pouring 100 ml of water suspension of R. solanacarum (108 cfu/ml) on the roots. Completely Randomized Design (CRD) was used in this experiment. The scoring observation was carried out every week for one month. This study showed that Permata as a control was the most resistant, while Timoti and H-7996 were medium resistant. The CLN, G6, G8, and G7 lines were susceptible medium, yet only G8 and G7 with the smallest percentage of disease intensity and not significantly different than Timoti. The resistance gene to bacterial wilt on H-7996 was controlled by genes in the cell nucleus with additive-dominant gene action. Resistance to bacteria has a moderate level of heritability.